The P300 Event-Related Potential Component and Cognitive Impairment in Epilepsy: A Systematic Review and Meta-analysis - Zhong, Rui; Li, Mengmeng; Chen, Qingling; Li, Jing; Li, Guangjian; Lin, Weihong (Frontiers in Neurology, 2019)
Abstract Background Epilepsy is one of the most prevalent chronic brain diseases worldwide and is often accompanied by cognitive impairment. Event-related potentials (ERPs) are an objectively noninvasive approach for studying information processing and cognitive functions in the brain. The P300 is an important and extensively explored late component of ERPs that has been widely applied to assess cognitive function in epilepsy in previous studies. However, consistent conclusions have not yet been reached for various reasons. Objective We conducted a comprehensive systematic review and meta-analysis of P300-related studies to assess the latency and amplitude of the P300 in epileptic patients. Methods PubMed, EMBASE, and Cochrane Library databases were systematically searched for eligible studies. The standard mean difference (SMD) and the 95% confidence interval (CI) were calculated as the effect size of the P300 component. Results The main results of the present meta-analysis indicated that epileptic patients have a longer P300 latency and a lower P300 amplitude than controls. Subgroup analysis based on age group demonstrated that these differences can be observed in both children and adult patients compared with healthy controls. In addition, the P300 latency was longer in patients with the five main types of epileptic seizures than in controls. Conclusion This study revealed that epileptic patients have abnormalities in the P300 component, which may reflect deficits in cognitive function. Thus, the P300 may be a potential objective approach for evaluating cognitive function in epileptic patients.